2016
DOI: 10.4236/ns.2016.81001
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-18 Radiochemistry: A Novel Thiol-Reactive Prosthetic Group, [18F]FBAMPy

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…T. M. Moore et al reported another derivative of this thiol-reactive prosthetic group, 2-[ 18 F]FBAMPy, with a decay corrected yield of 30 ± 4% in 80 minutes of synthesis time. 12…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…T. M. Moore et al reported another derivative of this thiol-reactive prosthetic group, 2-[ 18 F]FBAMPy, with a decay corrected yield of 30 ± 4% in 80 minutes of synthesis time. 12…”
Section: Resultsmentioning
confidence: 99%
“…3,4 [ 18 F]Fluorobenzaldehydes are also used in the synthesis of maleimide functionalized fluorine-18 labeling agents, another important class of radiolabeling synthons for site specific labeling of biomolecules via coupling with a thiol group. A variety of fluorine-18 labeled maleimide functionalized prosthetic groups have been developed over the last few years, eg, 2- 12 17,18 and N-(2-(2,5-dioxo-2,5-dihydro-1Hpyrrol-1-yl)-ethyl)-6-fluoronicotinamide ([ 18 F]FNEM). 19 Preparation of any of these compounds requires a 2step or 3-step synthesis with overall preparation times ranging from 60 to 90 minutes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These prosthetic groups are catego-rized into three classes amine, thiol and carboxylic reactive. Notable thiol reactive bifunctional agents include [ 18 F] FBAM [5] [6], [ 18 F]FBOM [7], [ 18 F]FBABM [8], [ 18 F]FPyAM [9] and [ 18 F]FPyMe [10] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%